2022
DOI: 10.1111/1365-2656.13783
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal connectivity dynamics in spatially structured populations

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…demographic consequences) and gene flow (i.e. evolutionary consequences) and their variation in space and time (Peniston et al 2019, Drake et al 2022a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demographic consequences) and gene flow (i.e. evolutionary consequences) and their variation in space and time (Peniston et al 2019, Drake et al 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing recognition of the importance of considering the influence of demography in dispersal dynamics and their consequences on population dynamics was recently reviewed by Drake et al (2022b) who further emphasize the value of considering the 'demographically-weighted connectivity' (which they define as 'an extended conceptual representation of landscape connectivity that considers, explicitly, the population dynamics and demographics'). It has also been empirically demonstrated that considering connectivity patterns as coming from the spatial structure of a landscape is critical to better understand demographic dynamics of populations (Drake et al 2022a). In addition to demography, we emphasize the relevance of studying the spatial structure of genetic traits of interconnected populations in order to understand the evolutionary and demographic trajectories of local populations.…”
Section: Spatial Configuration Influences Local Populations Evolution...mentioning
confidence: 99%